Structural mechanism of DDX39B regulation by human TREX-2 and a related complex in mRNP remodeling - Bradley P. Clarke; Shengyan Gao; Menghan Mei; Dongqi Xie; Alexia E. Angelos; Ashley Vazhavilla; Pate S. Hill; Tolga Cagatay; Kimberly Batten; Jerry W. Shay; Yihu Xie; Beatriz M. A. Fontoura; et al. (Nature Communications)
Abstract Nuclear export of mRNAs in the form of messenger ribonucleoprotein particles (mRNPs) is an obligatory step for eukaryotic gene expression. The DEAD-box ATPase DDX39B (also known as UAP56) is a multifunctional regulator of nuclear mRNPs. How DDX39B mediates mRNP assembly and export in a controlled manner remains elusive. Here, we identify a novel complex TREX-2.1 localized in the nucleus that facilitates the release of DDX39B from the mRNP. TREX-2.1 is composed of three subunits, LENG8, PCID2, and DSS1, and shares the latter two subunits with the nuclear pore complex-associated TREX-2 complex. Cryo-EM structures of TREX-2.1/DDX39B and TREX-2/DDX39B identify a conserved trigger loop in the LENG8 and GANP subunit of the respective TREX-2.1 and TREX-2 complex that is critical for DDX39B regulation. RNA sequencing from LENG8 knockdown cells shows that LENG8 influences the nucleocytoplasmic ratio of a subset of mRNAs with high GC content. Together, our findings lead to a mechanistic understanding of the functional cycle of DDX39B and its regulation by TREX-2 and TREX-2.1 in mRNP processing.